ANALISIS KINERJA PERBANKAN SYARIAH DI INDONESIA MENGGUNAKAN KONSEP SHARIAH MAQASHID INDEX - Mira Munira; Shinta Budi Astuti; Ameilia Damayanti (RELEVAN : Jurnal Riset Akuntansi, 2022)
This study aimed to analyze the performance based on the concept of Maqashid Syariah using SMI (Shariah Maqashid Index) Value. This study is used data from financial report and annual report which were provided by each Islamic Bank sample. The whole samples is consist of 6 Islamic Banks in Indonesia during five years period (2016-2020). The analytical method in this study is Descriptive Test. Based on the results of the study, it can be concluded that the highest ranking performance of Islamic banking in Indonesia is achieved by BTPN Syariah